If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -6) = 6(x + 4) Reorder the terms: 2(-6 + x) = 6(x + 4) (-6 * 2 + x * 2) = 6(x + 4) (-12 + 2x) = 6(x + 4) Reorder the terms: -12 + 2x = 6(4 + x) -12 + 2x = (4 * 6 + x * 6) -12 + 2x = (24 + 6x) Solving -12 + 2x = 24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -12 + 2x + -6x = 24 + 6x + -6x Combine like terms: 2x + -6x = -4x -12 + -4x = 24 + 6x + -6x Combine like terms: 6x + -6x = 0 -12 + -4x = 24 + 0 -12 + -4x = 24 Add '12' to each side of the equation. -12 + 12 + -4x = 24 + 12 Combine like terms: -12 + 12 = 0 0 + -4x = 24 + 12 -4x = 24 + 12 Combine like terms: 24 + 12 = 36 -4x = 36 Divide each side by '-4'. x = -9 Simplifying x = -9
| 6j+5=4j-7 | | -3(2x-4)=4(1.5x-3) | | -3(2x-4)=4((3/2x)-3) | | -70x+15=-23-18x | | -8/7-(-1/2) | | 2(15x-4)=8(3x+8) | | -1/9-(-2/15) | | -5.29-1.4d=-12.4d+12.3d+18.24 | | 6(x-2)=2x+7 | | 0.14y+0.09(y+7000)=2470 | | 5(x+10)=140 | | 3/4-(-1/9) | | X+8+3x+2=90 | | 5r+4=2r+46 | | 5x+0.3=20.3 | | f(-3)=9-4(-3)+6 | | x^3a+bx+c=0 | | 160=-9d+7 | | 1.32=x-0.2x | | a+bx+cx^3=c | | 2(-8)-15=6(-8)+17 | | -(p-3)=-3(1+p) | | -6(-6-6k)-3k=16+7k | | 19=9r-8 | | 15.6b+0.03=10.35+16.4b | | 35=9r-10 | | 7/10x=332 | | -7/6-(-3/4) | | -7/6--3/4 | | 19f=15f-20 | | -11r=-33 | | -5x+6x+15-3x=-3 |